Study of antimicrobial characteristics of spices composition - Teterina, Svitlana; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana; Khlystun, Irina (My University, 2015)
In order to produce safe, high-quality milk and cultured milk foods with a prolonged storage period it is important to inhibit the development of microorganisms. The research aims to study the effects of previously developed spice aromatic composition on test cultures of microorganisms (samples of contaminating microflora), such as Enterobactercloaceae, Micrococcus albus, Bacillus subtilis, Endomyceslactis. The spice composition contains ginger, cinnamon, cloves, curcuma, sumac, anise, black pepper and sweet pepper, cardamom, fenugreek, nutmeg and badiane (star anise).
Keywords: антимікробна дія; кисломолочні продукти; прянощі; antimicrobial characteristics; fermented milk products; spices; кафедра технології молока і молочних продуктів; кафедра біотехнології і мікробіології